Factors That Influencing Interest in Implementing Accounting Through Digital Financial Recording - Muhammad Syahrul Mubarok; Achmad Wicaksono; Kafidin Muzakki; Chairil Anwar (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
Research Objectives: The purpose of this study is to analyze the influence of accounting knowledge, subjective norms and control perspectives on interest in implementing accounting through digital financial recording in MSMEs in Kepadangan village. Design/methodology/approach: To answer the hypothesis about this see, the statistical analysis method used is to apply multiple linear regression. Research Findings: The population in this study is all MSME actors in Kepadangan Village whose commercial business is within the scope of the cooperative office totaling 208 MSMEs. The slovin formula is the calculation used in determining this sample, the sampling method is simple random sampling so that the sample amounts to 68 MSMEs. The result of this observation is that accounting knowledge and behavioral control perspectives have a positive influence on interest in carrying out accounting through virtual economy information. Meanwhile, subjective norms have no effect on hobbies in the use of accounting through virtual programs. Limitations and implications of the research: This study is predicted to provide consideration for MSME actors in Kepadangan Village that with adequate expertise and experience in the field of accounting, they can use accounting information well and can produce monetary evaluations so that monetary records can be recorded properly